Escherichia coli Nth and human hNTH1 DNA glycosylases are involved in removal of 8-oxoguanine from 8-oxoguanine/guanine mispairs in DNA - Matsumoto, Yukiko (Oxford University Press, 2001)
The spectrum of DNA damage caused by reactive oxygen species includes a wide variety of modifications of purine and pyrimidine bases. Among these modified bases, 7,8-dihydro-8-oxoguanine (8-oxoG) is an important mutagenic lesion. Base excision repair is a critical mechanism for preventing mutations by removing the oxidative lesion from the DNA. That the spontaneous mutation frequency of the Escherichia coli mutT mutant is much higher than that of the mutM or mutY mutant indicates a significant potential for mutation due to 8-oxoG incorporation opposite A and G during DNA replication. In fact, the removal of A and G in such a situation by MutY protein would fix rather than prevent mutation. This suggests the need for differential removal of 8-oxoG when incorporated into DNA, versus being generated in situ. In this study we demonstrate that E.coli Nth protein (endonuclease III) has an 8-oxoG DNA glycosylase/AP lyase activity which removes 8-oxoG preferentially from 8-oxoG/G mispairs. The MutM and Nei proteins are also capable of removing 8-oxoG from mispairs. The frequency of spontaneous G:C→C:G transversions was significantly increased in E.coli CC103mutMnthnei mutants compared with wild-type, mutM, nth, nei, mutMnei, mutMnth and nthnei strains. From these results it is concluded that Nth protein, together with the MutM and Nei proteins, is involved in the repair of 8-oxoG when it is incorporated opposite G. Furthermore, we found that human hNTH1 protein, a homolog of E.coli Nth protein, has similar DNA glycosylase/AP lyase activity that removes 8-oxoG from 8-oxoG/G mispairs.